The roles and applications of short-chain fatty acids derived from microbial fermentation of dietary fibers in human cancer - Li, Yuanqing; Huang, Yaxuan; Liang, Haili; Wang, Wen; Li, Bo; Liu, Ting; Huang, Yuqi; Zhang, Zhe; Qin, Yutao; Zhou, Xiaoying; Wang, Rensheng; Huang, Tingting (Frontiers in Nutrition, 2023)
Dietary fibers (DFs) and its metabolites attract significant attention in research on health and disease, attributing to their effects on regulating metabolism, proliferation, inflammation, and immunity. When fermented by gut microbiota, DFs mainly produce short-chain fatty acids (SCFAs), such as acetic acid, propionic acid, and butyric acid. As the essential nutrients for intestinal epithelial cells, SCFAs maintain intestinal homeostasis and play essential roles in a wide range of biological functions. SCFAs have been found to inhibit histone deacetylase, activate G protein-coupled receptors, and modulate the immune response, which impact cancer and anti-cancer treatment. Notably, while extensive studies have illuminated the roles of SCFAs in colorectal cancer development, progression, and treatment outcomes, limited evidence is available for other types of cancers. This restricts our understanding of the complex mechanisms and clinical applications of SCFAs in tumors outside the intestinal tract. In this work, we provide a comprehensive summary of the latest evidence on the roles and mechanisms of SCFAs, with the focus on butyric acid and propionic acid, derived from microbial fermentation of DFs in cancer. Additionally, we recapitulate the clinical applications of SCFAs in cancer treatments, and offer our perspectives on the challenges, limitations, and prospects for utilizing SCFAs in cancer research and therapy.